Uma nova abordagem da recomendação ITU-R P.1546 para a predição de cobertura em enlaces curtos sobre terrenos mistos - Marco Antonio de Souza Mayrink (2005)
The International Telecommunication Union has in the Recommendation ITU-R P.1546 a method for point-to-area predictions for terrestrial services in the frequency range 30 MHz to 3000 MHz. That recommendation was proposed to mitigate known limitations associated to distances and frequencies range, combining several existent methods in one. In the present work, motivated by an acquainted deficiency of the recommendation in the covering prediction for short mixed-paths with a clear line-of-sight, we suggest an improvement of the recommendation in what concerns the treatment of these paths, based on the intersection of the first Fresnels ellipsoid and terrain profile. A software was developed for the simulation of the models and some preliminary results (measured and theoretical) accomplished in the cities of Belo Horizonte-MG and Brasilia-DF are presented and discussed.